Swedish Ambulance Managers' Descriptions of Crisis Support for Ambulance Staff After Potentially Traumatic Events. Issue 6 (10th October 2014) - Hugelius, Karin; Berg, Sara; Westerberg, Elin; Gifford, Mervyn; Adolfsson, Annsofie
Abstract Introduction Ambulance staff face complex and sometimes stressful or potentially traumatic situations, not only in disasters but also in their routine daily work. The aim of this study was to survey ambulance managers' descriptions of crisis support interventions for ambulance staff after potential traumatic events (PTEs). Methods Semistructured interviews with a qualitative descriptive design were conducted with six ambulance managers in a health care region in central Sweden. The data was analyzed using content analysis. Result Five categories were found in the result: (1) description of a PTE; (2) description and performance of crisis support interventions; (3) impact of working in potentially traumatic situations; (4) the ambulance managers' role in crisis support interventions; and (5) the ambulance managers' suggestions for improvement. Ambulance managers described crisis support interventions after a PTE as a single, mandatory group meeting with a structure reminiscent of debriefing. The ambulance managers also expressed doubts about the present structures for crisis support and mentioned an alternative approach which is more in line with present evidence-based recommendations. Conclusion The results indicated a need for increased understanding of the importance of the managers' attitudes for ambulance staff; a need for further implementation of evidence-based recommendations for crisis support interventions was also highlighted. <mixed-citation id="ref" publication-type="journal"> <string-name> <given-names>K</given-names> <x content-type="archive" xml:space="preserve"> </x> <surname>Hugelius</surname> </string-name>, <string-name><given-names>S</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Berg</surname></string-name>, <string-name><given-names>E</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Westerberg</surname></string-name>, <string-name><given-names>M</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Gifford</surname></string-name>, <string-name><given-names>A</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Adolfsson</surname></string-name>. Swedish ambulance managers' descriptions of crisis support for ambulance staff after potentially traumatic events . <source>Prehosp Disaster Med</source>. <year>2014</year>;<volume>29</volume>(<isbn>6</isbn>):<fpage>1</fpage>-<lpage>4</lpage></mixed-citation>.